Leadership of Winter Mixed-Species Flocks by Tufted Titmice (Baeolophus bicolor): Are Titmice Passive Nuclear Species? - Contreras, Thomas A.; Sieving, Kathryn E. (International Journal of Zoology, 2011)
The tufted titmouse (Baeolophus bicolor, TUTI) is a nuclear species in winter foraging flocks whose antipredator calls are used to manage predation risk by diverse heterospecifics. We hypothesized that satellite species in mixed flocks follow TUTI (not vice versa), thereby defining the role of TUTI as a “passive” nuclear species. We followed 20 winter mixed-species flocks in North-Central Florida and assessed angular-angular correlations between overall flock, TUTI, and satellite species movement directions. We observed significant correlations between overall flock movement directions and those of TUTI, confirming our central prediction. Within flocks, however, fine-scale movement directions of satellite species were often more highly correlated with those of other satellites than with TUTI movements. We conclude that TUTI are passive nuclear species whose movements define flock paths, but within flocks, TUTI movements may have less influence on satellite movements than do other factors.